2015
DOI: 10.3791/53376
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Recovery after Merging a Droplet to Measure the Two-dimensional Diffusion of a Phospholipid Monolayer

Abstract: We introduce a new method to measure the lateral diffusivity of a surfactant monolayer at the fluid-fluid interface, called fluorescence recovery after merging (FRAM). FRAM adopts the same principles as the fluorescence recovery after photobleaching (FRAP) technique, especially for measuring fluorescence recovery after bleaching a specific area, but FRAM uses a drop coalescence instead of photobleaching dye molecules to induce a chemical potential gradient of dye molecules. Our technique has several advantages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…The amount of rhodamine on the giant lipid vesicles showed that the fusion of the LUVs to the lipid droplet was greater than that of the LUVs to the giant lipid vesicles ( Figure 3 a–c). The difference in fusion between the LUVs and the lipid droplet and between the LUVs and the giant lipid vesicle was attributable to the lipid diffusion of the lipid droplet and the giant lipid vesicle; the lipid diffusion of the lipid droplet was higher than that of the giant lipid vesicle [ 22 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…The amount of rhodamine on the giant lipid vesicles showed that the fusion of the LUVs to the lipid droplet was greater than that of the LUVs to the giant lipid vesicles ( Figure 3 a–c). The difference in fusion between the LUVs and the lipid droplet and between the LUVs and the giant lipid vesicle was attributable to the lipid diffusion of the lipid droplet and the giant lipid vesicle; the lipid diffusion of the lipid droplet was higher than that of the giant lipid vesicle [ 22 , 23 ].…”
Section: Resultsmentioning
confidence: 99%